The association between fundamental athletic movements and physical fitness in elite junior Australian footballers. Issue 4 (16th February 2018) - Woods, Carl T.; McKeown, Ian; Keogh, Justin; Robertson, Sam
ABSTRACT: This study investigated the associations between fundamental athletic movement and physical fitness in junior Australian football (AF). Forty-four under 18 players performed a fundamental athletic movement assessment consisting of an overhead squat, double lunge, single leg Romanian deadlift and a push up. Movements were scored on three assessment criterions using a three-point scale. Additionally, participants performed five physical fitness tests commonly used for talent identification in AF. A Spearman's nonparametric correlation matrix was built, with correlation coefficients being visualised using a circularly rendered correlogram. Score on the overhead squat was moderately positively associated with dynamic vertical jump height on left ( r s  = 0.40; P  ≤ 0.05) and right ( r s  = 0.30; P  ≤ 0.05) leg take-off, stationary vertical jump ( r s  = 0.32; P  ≤ 0.05) and negatively associated with 20-m sprint time ( r s  = −0.35; P  ≤ 0.05). Score on the double lunge (left/right side) was moderately positively associated with the same physical fitness tests as well as score on the multistage fitness test. Results suggest that improvements in physical fitness qualities may occur through concurrent increases in fundamental athletic movement skill, namely the overhead squat and double lunge movements. These findings may assist with the identification and development of talent.